Pengaruh Penggunaan Quizizz Terhadap Hasil Belajar IPA di SDN Cipinang Melayu 10 Pagi - Prayoga Yulistiadi Yulistiadi; Lelly Qodariah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study is intended to analyze and find out whether or not there is an average influence of the learning outcomes of grade 5 students in the use of the Quizizz platform in learning Sciences (IPA) at SDN Cipinang Melayu 10 Pagi. The use of the method is carried out using the True Experimental Design method of the Pretest-Posttest Control Group design. The sample of the study was carried out consisting of 48 students, classes 5A and 5B. The type of test instrument performed is a multiplechoice test. Data analysis techniques were carried out using the help of Microsoft Excel, and also SPSS 26.0 in normality tests using the Kolmogorov-Smirnov test, levene test, and independent sample t-test. The results of the study obtained there was no difference in the average learning outcomes of science using the Quizizz platform and also conventional methods, obtained in the t-test hypothesis test showed a value of 0.482 at α = 0.05. So that H0 is accepted and H1 is rejected so that it shows that there is no difference in the average results of learning science in grade 5 SDN Cipinang Melayu 10 Pagi which is significant.